PERSEPSI GENERASI MUDA (MAHASISWA FISIP UNIVERSITAS RIAU) TERHADAP BATIK - Oktri Permata Lani (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
Batik is one of the cultural icons of Indonesia which is known by the whole world. Batik is the national identity of our nation, namely the manifestation of values that grow and develop in aspects of the life of a nation. The current phenomenon of the younger generation and adults no longer has a sense of interest and interest in indigenous Indonesian culture. Even worse, there are some groups who are apathetic to their own culture. Therefore, this study aims to look at the development of culture among Indonesian youth, by looking at the Young Generation's Perception of Batik. Methods This research uses qualitative methods which aim to be able to describe according to what the researchers in the field are studying. To obtain data using three ways, namely by observation techniques, interview techniques, and documentation techniques, namely the perception of students of FISIP, Riau University. The results of this study are positive perceptions of batik from FISIP UR students are loving batik not only because it is a legacy of wealth from their ancestors. Meanwhile, the negative perception regarding ibat is that batik is considered only an ancestral heritage